PERSON-ENVIRONMENT FIT AND ITS DIMENSIONS AS PREDICTORS OF HYGIENE FACTORS AMONG THE CEBU INSTITUTE OF TECHNOLOGY-UNIVERSITY EMPLOYEES - Florabel H. Chua and Ronald C. Yrog-irog (Chelonian Research Foundation, 2024)
This study investigates the influence of Person-Environment Fit (PE Fit) on Hygiene Factors among the employees of Cebu Institute of Technology-University (CIT University) during the 2023 to 2024 academic year. Utilizing the Perceived Person-Environment Fit Scale (PPEFS) and Bellingham’s Job Satisfaction Survey, data was collected from 278 respondents through a descriptive predictive survey design. Findings suggest a predominantly positive alignment between employee perceptions and their work environment, with variations noted in Person-Supervisor Fit. While overall Hygiene Factors received high agreeability, areas for improvement were identified in Compensation, Benefits, and Personal (Work-life Balance). Notably, higher levels of P-E Fit correlated with increased satisfaction with Hygiene Factors, highlighting the importance of value alignment. The study emphasizes the significance of Person-Organization Fit and Person-Supervisor Fit in shaping employee satisfaction and recommends further research to explore demographic considerations. Recommendations include revamping communication channels, aligning organizational values, enhancing supervisor training, optimizing compensation and benefits, and promoting work-life balance initiatives to foster a supportive and fulfilling work environment at CIT University.